PENERAPAN KEAMANAN DATA DENGAN MENGGUNAKAN METODE CAESAR CHIPER UNTUK MENGAMANKAN DATABASE MYSQL - Meriska Hamni; Muhammad Khairul Amri; Sherly Rezeky; Adnan Buyung Nasution (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Security issues are not a concern for most database managers. Despite the fact that database security is very important because data can be stolen from databases that have no security. In addition, the database can be accessed directly by opening a database application such as MySQL which can be opened on localhost, making it easier for thieves or information destroyers to change or damage it and browse the database directly. Database security previously relied solely on authentication systems, which had the disadvantage that someone could find out passwords and cause identity impersonation. Cryptography is the method that researchers use in this regard. It is anticipated that the contents of the MySQL database will receive increased security thanks to the Caesar Cipher method. By using the MySQL database application and the Visual Basic 2010 application program, a program can be created that can secure the MySQL database. The benefit is that the application can protect data sets with two easy-to-use code techniques. However, security is very good. Naturally, the goal is to protect the MySQL database from information thieves.